2 - The Contradictory Position of 'Tradition' in African Nationalist Discourse: Some Analytical and Political Reflections* - Neocosmos, Michael (Africa Development, 2022)
In the immediate post-colonial period, 'tradition' was seen by African national ism both as the basis of an authentic indigenous culture to be celebrated and opposed to a hegemonic Western (globalised) culture, and as a backward for mation created (or manipulated) by Western (neo) colonialism to divide and rule and thus as inimical to 'modern' nation-state formation. An idealised tradition thus held a contradictory location within what came to be state nationalist discourse, as exhibiting both potentially liberatory and repressive features si multaneously. Different aspects of an idealised 'tradition' were drawn upon by different post-colonial leaders at different ends of the political spectrum in their attemptiat nation-building and in order to legitimise different forms of authori tarian developmentalism (eg. Nyerere's 'Ujamaa' and Mobutu's 'Authenticité'). Some were evidently more successful than others, but broadly, such attempts bore witness to the continued and unwavering legitimacy of tradition among the populations of the continent. There is no evidence that this legitimacy has de clined today despite the evident failure of state nationalism. The contradictory character of tradition in Africa is also reflected today in the views of African scholars where some intellectuals stress that tradition forms the basis for a 'de centralized despotism' inherited from the colonial period, while others visualise it as forming the site of a 'convivial' alternative to Western individualism and globalizing culture or even as containing the possible model for a alternative to liberalism. Moreover, tradition often finds itself at the end of a powerful critique by human rights discourse supported by li nism inter alia. This paper addresses this central issue and sheds lig possible place of tradition within an alternative popular-nationalist di the continent. It suggests that the dominant trend within the nationalis 1950s and 1960s (from which emerged the dominant state-nationalist p in the immediate post-colonial period) operated very much within the context of a hegemonic liberal conception of politics and state-fonnation, and as unable to overcome this contradiction. The paper argues for the nece democratic struggle within tradition itself (as well as within rights) a against both the uncritical celebration of tradition as an essentially au ture, as well as its undermining from 'beyond its boundaries' by libe discourse. An alternative look at 'tradition' in Africa requires that it stood from within the perspective of an altogether new way of think politics, in particular this means an understanding for which democr equated with human rights. A critical engagement with tradition must fo a questioning of human rights discourse from the perspective of the majority in Africa.